Avoiding nocebo and other undesirable effects in chiropractic, osteopathy and physiotherapy: An invitation to reflect. (December 2022) - Hohenschurz-Schmidt, David; Thomson, Oliver P.; Rossettini, Giacomo; Miciak, Maxi; Newell, Dave; Roberts, Lisa; Vase, Lene; Draper-Rodi, Jerry
Abstract: Introduction: While the placebo effect is increasingly recognised as a contributor to treatment effects in clinical practice, the nocebo and other undesirable effects are less well explored and likely underestimated. In the chiropractic, osteopathy and physiotherapy professions, some aspects of historical models of care may arguably increase the risk of nocebo effects. Purpose: In this masterclass article, clinicians, researchers, and educators are invited to reflect on such possibilities, in an attempt to stimulate research and raise awareness for the mitigation of such undesirable effects. Implications: This masterclass briefly introduces the nocebo effect and its underlying mechanisms. It then traces the historical development of chiropractic, osteopathy, and physiotherapy, arguing that there was and continues to be an excessive focus on the patient's body. Next, aspects of clinical practice, including communication, the therapeutic relationship, clinical rituals, and the wider social and economic context of practice are examined for their potential to generate nocebo and other undesirable effects. To aid reflection, a model to reflect on clinical practice and individual professions through the 'prism' of nocebo and other undesirable effects is introduced and illustrated. Finally, steps are proposed for how researchers, educators, and practitioners can maximise positive and minimise negative clinical context.